Correlation between personality traits of young athletes and their level of self efficacy - Halian, I.; Popovych, I.; Hulia, I.; Serbin, I.; Vyshnevska, O.; Pyslar, A. (Journal of Physical Education and Sport, 2023)
The purpose is to examine a correlation of personality traits of young athletes with different levels of self efficacy components (n=114). We assume that self-efficacy of young athletes depends on their personality traits. However, there are differences in the research participants with high and low levels of self-efficacy.